Questionnaire for digital technologies and leadership practices: the validity and reliability study - Antonios Kokkonos; Antonios Travlos; Panagiota Antonopoulou; Maria Pavlis Korre (Institute of Advanced Engineering and Science, 2025)
The exponential progress and massive utilization of digital technologies has significant implications for leadership theory and for leadership practices that remain unexplored in the current literature. This study provides insights into the validity and reliability of the questionnaire for digital technologies and leadership practices (QDTLP), through research conducted in 215 elementary schools in the Peloponnese region of Greece. The research consists of three parts: i) a pilot study to assess the stability and reliability of the initial QDTLP version; ii) study 1 to examine the validity and reliability using exploratory and confirmatory factor analysis; and iii) study 2 to further assess the validity and reliability using confirmatory factor analysis (CFA). The QDTLP was designed and developed after a systematic literature review in the field of digital technologies and school leadership practices, to investigate if, and to what extent, the utilization of digital technologies affects the leadership practices in elementary schools. The research findings provide strong evidence for content and construct validity as well as reliability of the 4-factor and 22-item QDTLP research instrument.